User-controllable personalization: A case study with SetFusion. Issue 78 (June 2015) - Parra, Denis; Brusilovsky, Peter
Abstract: In this research we investigated the role of user controllability on personalized systems by implementing and studying a novel interactive recommender interface, SetFusion. We examined whether allowing the user to control the process of fusing or integrating different algorithms (i.e., different sources of relevance) resulted in increased engagement and a better user experience. The essential contribution of this research stems from the results of a user study ( N =40) of controllability in a scenario where users could fuse different recommendation approaches, with the possibility of inspecting and filtering the items recommended. First, we introduce an interactive Venn diagram visualization, which combined with sliders, can provide an efficient visual paradigm for information filtering. Second, we provide a three-fold evaluation of the user experience: objective metrics, subjective user perception, and behavioral measures. Through the analysis of these metrics, we confirmed results from recent studies, such as the effect of trusting propensity on accepting the recommendations and also unveiled the importance of features such as being a native speaker. Our results present several implications for the design and implementation of user-controllable personalized systems. highlights: We explored user-controllable interfaces as extension of traditional-ranked lists. We introduced SetFusion, a controllable interface with sliders and a Venn diagram. We conducted a controlled user study on online conference article recommendation. Our evaluation had three dimensions: users' perception, behavioral and IR metrics. Controllable interface had a positive effect influenced by users' characteristics.